2007
DOI: 10.17221/1850-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternative organic fertilizers on the nutritional value and yield of head cabbage

Abstract: Commercial brands of alternative, organic fertilizers were compared with conventional, mineral fertilizers using head cabbage. There were six different treatments: conventional farmyard manure, Agro (made from poultry bedding and molasses), Dvorecký agroferm (granulated, made from dried, aerobically-fermented farmyard manure), Agormin (an organo-mineral fertilizer), compost manufactured from plant waste material, mineral fertilizer, and an unfertilized control. All the treatments were applied at rates providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This finding is similar to that obtained in cabbage (Smith andHadley, 1988 andZahradnik andPetrikova, 2007). Zahradnik and Petrikova, (2007) found in head cabbage that Mg content was, significantly, higher when the organic fertilizers were used compared with mineral fertilizers.…”
Section: (B) Effect Of Organic Nitrogen Fertilizer (Chicken Manure) Rsupporting
confidence: 90%
“…This finding is similar to that obtained in cabbage (Smith andHadley, 1988 andZahradnik andPetrikova, 2007). Zahradnik and Petrikova, (2007) found in head cabbage that Mg content was, significantly, higher when the organic fertilizers were used compared with mineral fertilizers.…”
Section: (B) Effect Of Organic Nitrogen Fertilizer (Chicken Manure) Rsupporting
confidence: 90%
“…is agrees with the findings of Mehasen et al [24] that application of sheep manure compost contributed greatly to the cotton growth compared to control. e beneficial effects of organic manure on crop have also been well reported [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, Yamazaki and Roppongi (1998) and El-Shabrawy et al (2005) reported that organic manure increased N, P and K contents in head cabbage. However, Zahradník and Petříková (2007) found that application of compost had no significant effect on K content in cabbage leaves. As regard to nitrate accumulation, these data are in harmony with those obtained by Rubeiz et al (1993) who reported that organic produced cabbage contained a high concentration of NO3.…”
Section: N P K and No3 Accumulationmentioning
confidence: 94%